Fluorine-containing drugs approved by the FDA in 2019 - Mei, Haibo; Remete, Attila Márió; Zou, Yupiao; Moriwaki, Hiroki; Fustero, Santos; Kiss, Lorand; Soloshonok, Vadim A.; Han, Jianlin (Chinese chemical letters, 2020)
Eleven new fluorine-containing FDA-approved pharmaceuticals are discussed. Therapeutic areas of these newly developed fluorinated pharmaceuticals include schizophrenia, migraine, multiple sclerosis, insomnia, rheumatoid arthritis, anti-tuberculosis, breast cancer, lymphoma kinase inhibitor and serotonin receptor antagonist. [Display omitted] Eleven new fluorine-containing FDA-approved drugs have been profiled and details of their discovery and preparation are discussed. Therapeutic areas include schizophrenia, migraine, multiple sclerosis, insomnia, rheumatoid arthritis, anti-tuberculosis, breast cancer, lymphoma kinase inhibitor, serotonin receptor antagonist. New pharmaceuticals feature four examples of aromatic fluorine, three aromatic CF3 group, three aliphatic CF3 and one compound with aromatic CF3O group. Furthermore, among the new compounds, six are chiral and seven are derived from tailor-made amino acids.